2016
DOI: 10.3390/ijms17040592
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of STEAP1 Expression Determined via Immunohistochemistry Staining in Predicting Prognosis of Primary Colorectal Cancer: A Survival Analysis

Abstract: STEAP1 (six transmembrane epithelial antigen of the prostate 1) is a transmembrane protein that functions as a potential channel or transporter protein. It is overexpressed in certain cancers and is viewed as a promising therapeutic target. However, the prognostic role of STEAP1 is still controversial, and no role for STEAP1 has yet been indicated in colorectal cancer. The aim of this study was to investigate the possible association of STEAP1 expression with colorectal cancer prognosis. STEAP1 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…It was proved that the expression of STEAP1 in prostate cancer is significantly increased, and silencing STEAP1 expression can inhibit the proliferation of prostate cancer cells and promote apoptosis [10]. Furthermore, the upregulation of STEAP1 has been also detected in lung, gastric, colorectal, renal, and bladder cancer [28][29][30][31]. Maia et al demonstrated that STEAP1 is overexpressed in human breast cancer cases [32].…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that the expression of STEAP1 in prostate cancer is significantly increased, and silencing STEAP1 expression can inhibit the proliferation of prostate cancer cells and promote apoptosis [10]. Furthermore, the upregulation of STEAP1 has been also detected in lung, gastric, colorectal, renal, and bladder cancer [28][29][30][31]. Maia et al demonstrated that STEAP1 is overexpressed in human breast cancer cases [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dysregulation of the STEAP family (STEAP1, STEAP2, STEAP3, and STEAP4) has been observed in various cancers. STEAP1 is highly expressed in many human malignancies, including prostate, lung, bladder, colon, ovarian, and Ewing's sarcoma cancers [13] , [14] , [15] . Furthermore, STEAP1 has also been identified as an intriguing target for antibody therapy in multiple solid human tumors [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of STEAP1 was closely related to the malignant phenotype of cancer cells. [13,[16][17][18][19][20] However, in Lee's study, they found no correlation between expression of STEAP1 and the clinicopathological factors [21]. These con icting results indicated that the roles of STEAP1 were varied depending on different cancer types.…”
Section: Introductionmentioning
confidence: 89%